Peran Peran Kepuasan Dalam Memediasi Pengaruh “Online Review”, Kualitas Pelayanan, Dan Lokasi Terhadap Loyalitas Konsumen pada Restoran “Warong Legong” di Desa Keramas, Gianyar, Bali - Massenga, Lidjah Magdalena; Budiani, Ni Putu Ariesta; Ni Luh Suastuti; Pranadewi, Putu Mira Astuti; Arcana, I nyoman (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Online consumer reviews on Google Reviews, Zomato and Tripadvisor help restaurants monitor the quality standards of their products and services to consumers. In the face of increasingly tight competition, restaurants must pay attention to customer experience, in terms of product quality, price, strategic location, and service quality, so that customers feel satisfied with their dining experience. This study aims to analyze the role of satisfaction